Steric effects on complexation of bis(meta‐phenylene)‐32‐crown‐10 derivatives with paraquats. Issue 2 (16th January 2017) - Niu, Zhenbin; Huang, Feihe; Gibson, Harry W.
Abstract: Novel 5, 5′‐disubstituted BMP32C10 derivatives bearing different sized substituents were designed and prepared. The stoichiometries and complexation behavior between these hosts and paraquats were studied. It was found that bulky 5, 5′‐substituents disfavor complexation with paraquats by hindering the formation of [2]pseudorotaxane and "taco" complexes.